The Arabic Version of the Pittsburgh Fatigability Scale for Older Adults: Translation and Validation - Mutasim D. Alharbi; Fayaz Khan; Aya Saeb; Nancy W. Glynn; Baian A. Baattaiah (BMC Geriatrics)
Abstract Background The Pittsburgh Fatigability Scale (PFS) was developed to assess perceived physical and mental fatigability in older adults (≥ 60 years). No perceived fatigability questionnaire has been validated to date for use among the Arabic older adult population. The aim of this study was to translate the PFS into Arabic language, and to assess the reliability and validity of the translated version among an Arabic older adult population. Methods The primary design of this methodological study was cross-sectional. The PFS was translated into Arabic using the forward-backward translation method according to established guidelines. Internal consistency was evaluated by Cronbach’s alpha coefficient. The test-retest reliability was evaluated using intraclass correlation coefficients over a two-week interval. Construct validity was evaluated by exploratory and confirmatory factor analyses. The convergent and discriminant validity were measured by calculating Spearman’s correlation coefficients between the PFS– Arabic version and the Arabic versions of the Fatigue Severity Scale (FSS), Perceived Stress Scale (PSS), and WHO-5 Well-Being Index. Results The validity and reliability sample included 277 older adults with a mean age of 66.0 ± 5.3. For the PFS– Arabic version, the intraclass correlation coefficient for test-retest reliability for both the physical and mental subscale was high (0.97). Cronbach’s alpha for the PFS– Arabic version was 0.75 for the physical fatigability subscale and 0.71 for the mental fatigability subscale. The results of the factor analyses revealed that a four-factor model of PFS– Arabic version physical and mental subscales was a good model fit in our sample. Both subscales of PFS– Arabic version showed moderate correlation with FSS (r = 0.3, p < 0.0001) and weak correlation with PSS (r = 0.2). The WHO-5 showed a moderate correlation with PFS– Arabic Physical subscale (r = -0.3) and weak correlation with PFS– Arabic Mental subscale (r = -0.2). Conclusion The PFS– Arabic version showed good psychometric properties and is recommended for use among Arabic-speaking populations to assess perceived fatigability in older adults.